El desarrollo y dominio de las competencias Científico-profesionales del docente universitario. - Silva Bustillos, Ricardo (2015)
The knowledge society requires an intellectually independent professional to decide for himself, with responsibility, empathy, using the managed selfk now ledge and skills to critically submit their scientific and academic contributions in a reasoned manner, transmitting modes of intervention and Learning lifetime. The teacher fosters relationships and interactions between learner and teacher as organizer, counselor, facilitator between all these learners and to society through the process of learning to know cognitive to cognitive and be metacognitive. The change in attitude will develop and master skills methodological, communicative, technological epistemological, socio-professional, didactic teaching in teachers to get, A creative and respectful attitude foster a climate of empathy and equanimity towards different opinions, defend their thesis with arguments and accept the challenge, understand that there are different approaches to approach the study of the phenomenon